Identifying the Components of School-Based Curriculum Planning and Decentralization in Adolescents with Social Anxiety Symptoms - Gholami Mateki, Ramazan Ali; Hosseinzadeh, Babak; Hoseini Daronkala , Seyedeh Zahra (Assessment and Practice in Educational Sciences, 2025)
The objective of this study was to identify the core components of school-based curriculum planning and decentralization and to explore their role in enhancing the academic self-efficacy of adolescents with social anxiety symptoms. This study employed a qualitative research design based on semi-structured interviews with experienced principals of successful schools and educational experts from the Department of Education in Mazandaran Province, Iran. Participants were selected using purposive sampling with inclusion criteria of prior management or teaching experience, direct involvement in school-based curriculum planning, and willingness to participate. Data were collected through individual interviews lasting 25–45 minutes, during which participants shared their experiences regarding curriculum decentralization and its impact on teaching and learning. Interviews were audio-recorded with consent, transcribed verbatim, and analyzed using qualitative content analysis. Data coding followed iterative cycles of initial coding, category formation, and theme development, with validation through member checking, peer debriefing, and expert review to ensure credibility and trustworthiness. The analysis revealed four overarching themes and twenty-nine subthemes that collectively illustrate the relationship between curriculum decentralization and student outcomes. The main themes were structured curriculum design, collaborative and flexible implementation, growth-oriented and motivational evaluation, and empowering decentralization. In addition, eight detailed subthemes of decentralization were identified, including decision-making authority, structural flexibility, participatory governance, community engagement, alignment with policy frameworks, autonomy in learner evaluation, enrichment of resources, and strengthening professional identity. Together, these components demonstrated how school-based curriculum planning enhances self-efficacy and psychosocial resilience in adolescents, particularly those facing social anxiety. The study concludes that decentralization and school-based curriculum planning are mutually reinforcing processes that create adaptive, participatory, and context-sensitive learning environments. These environments not only improve institutional effectiveness but also play a critical role in fostering adolescents’ academic self-efficacy and reducing vulnerability to social anxiety.